BAURAN PROMOSI PADA PROGRAM STUDI ADIMINISTRASI BISNIS POLITEKNIK NEGERI BANJARMASIN - Cici Asmawatiy; Elfina Aliyati Rasyidi HB; Rizalul Gadi (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2022)
This study aims to determine the promotion mix at the Banjarmasin State Polytechnic Business Administration Study Program and to find out the obstacles faced and the efforts made related to the implementation of the Promotional Mix. This study uses descriptive methods, data collection techniques used are interviews, observations and documentation. While the data analysis technique used is qualitative analysis.The results of this study indicate that the Business Administration Study Program in carrying out promotional activities is said to be still less than optimal related to promotions that are carried out only limited to advertising and publicity that are not paid to attract new prospective students to the Business Administration Study Program, the obstacle faced is the limited funding for promotional activities, and efforts are being made to increase other promotional mix activities to support existing activities, namely collaborating on other study programs, utilizing assistance from the extended family of the Business Administration Study Program, conducting promotions in learning activities for students, one of whose duties is to design promotions. and carry out promotional activities from other mixes such as public relations and direct marketing.